2020
DOI: 10.1182/blood-2020-136193
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in Health-Related Quality of Life for Patients Treated with LentiGlobin for Sickle Cell Disease (bb1111) Gene Therapy

Abstract: Background In patients with sickle cell disease (SCD), health-related quality of life (HRQoL) is worse than in the general population and comparable or worse than in patients with other chronic or painful diseases such as cystic fibrosis or cancer. Targeting SCD pathophysiology may significantly improve HRQoL in addition to clinical outcomes. In the ongoing phase 1/2 HGB-206 Study (NCT02140554), which evaluates the safety and efficacy of LentiGlobin for SCD (bb1111) gene therapy (GT), the most r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…55,65 Other possible explanations include stigma related to the underlying illness (ie, SCD or TDT), the perceptions of being different, their dependence on parents in different daily activities, and losing social interactions with friends at and outside school for an extended period. 61 Nevertheless, it is also possible that HSCT may not have an expected impact on relational or social HRQOL outcomes. 61 The age at the time of HSCT is an important consideration when evaluating HRQOL outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…55,65 Other possible explanations include stigma related to the underlying illness (ie, SCD or TDT), the perceptions of being different, their dependence on parents in different daily activities, and losing social interactions with friends at and outside school for an extended period. 61 Nevertheless, it is also possible that HSCT may not have an expected impact on relational or social HRQOL outcomes. 61 The age at the time of HSCT is an important consideration when evaluating HRQOL outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…61 Nevertheless, it is also possible that HSCT may not have an expected impact on relational or social HRQOL outcomes. 61 The age at the time of HSCT is an important consideration when evaluating HRQOL outcomes. One study showed that patients with SCD or thalassemia who receive HSCT at an early age reported better HRQOL outcomes compared with those who received HSCT later in life, in particular after the age of 15 years.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations